The World Map by Anaximander (Miletus, 5th Century BC): Modeling geographical space at the beginning of science - Buzai, Gustavo Daniel (2021)
According to the Greeks science began in Miletus (Ionia) in the 6th century BC, linked to the need to provide rational explanations about the functioning of nature. In a context in which the mythical-religious perspective appeared with limited utility for a society that notably expanded its ethnocultural ties, Anaximander (610-546 BC) made important contributions to the understanding of the origin, the structure of the universe, the Earth and drafted the first map of the world in his book on nature. This study includes a hypothetical construction of the map and analyzes each of its components as concrete spatial elements of conceptual aspects that are present in the most distant antecedent of the modeling of geographic space within the framework of Geography as a spatial science.